Communication Theory in Construction of Communication Field. Reflections from History, Epistemology and Pedagogy - Rizo García, Marta (2014)
From the exhibition of some forms of organization communication theories, this text looks for to identify the theoretical foundations that they allow to characterize like interdisciplinary to the field of the communication, mainly marked by the contributions of social sciences like sociology, the economy and social psychology, among others. Once identified the main characteristics of the history of the communicational thought, some parameters set out to update the field of the theories of the communication, a dynamic and changing field, mainly by the own particularities of the communicative phenomenon, put under changes and continuous modifications. In last instance, some epistemological and pedagogical reflections consider that they try to help to make more dynamics communication theories field, from seeing the paper which they play in the construction of the study objects of the field and in the formation of professionals of the communication.